2000
DOI: 10.1002/1096-8644(200007)112:3<319::aid-ajpa4>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite variation in Central Africa: An analysis of intrapopulational and interpopulational genetic diversity

Abstract: As a part of a research project on molecular variation in Central Africa, we have analyzed 10 microsatellites (CD4, CSFO, D3S1358, D18S51, D21S11, F13A1, FES, TH01, TPOX, and VWA) in the Bamileke and Ewondo from Cameroon and the Sanga and Mbenzele Pygmies from the Central African Republic (a total of 390 chromosomes). A statistically significant trend towards heterozygote deficiency was detected in the Mbenzele Pygmies. This was established through the use of powerful exact tests for the Hardy-Weinberg equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…When compared to other populations, it was found that *16 is the most frequent vWA allele in Africans and African-Americans (0.261 to 0.371; Destro-Bisol et al, 2000). In the African descendant population of São Gonçalo, Bahia (Sousa, 2001) the allele *16 was also the most frequent (0.286).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…When compared to other populations, it was found that *16 is the most frequent vWA allele in Africans and African-Americans (0.261 to 0.371; Destro-Bisol et al, 2000). In the African descendant population of São Gonçalo, Bahia (Sousa, 2001) the allele *16 was also the most frequent (0.286).…”
Section: Resultsmentioning
confidence: 92%
“…There were no individuals classified as Amerindian or Caucasian by phenotype in this commuStudies in an African-descendant isolate 25 Sources: (1) Africans - (Deka et al, 1999;Destro-Bisol et al, 2000;Huguet et al, 1998;Bosh et al, 2001;Gene et al, 2001;Alves et al, 2001;Brinkmann et al, 1996;Brinkmann et al, 1998;Rolf et al, 1998;Wang et al, 2002;Pérez-Lezaun et al, 1997;Yunis et al, 2000;Corte-Real et al, 2000;Dios et al, 1998); (2) Europeans (Pérez- Lezaun et al, 2000;Anjos et al, 2000;Lourdes-Pontes et al, 1998;Asmundo et al, 1998;Santos et al, 1996;Souto et al, 1996, Souto et al, 1998Alves et al, 2001;Pinheiro et al, 1996;Amorim et al, 1996;Pereira et al, 1996;Gusmão et al, 1997;Espinheira et al, 1996;Miranda et al, 1998;Prata et al, 1998) nity. This date on phenotypic ethnic classification is based on facial morphological characteristics and skin color in body regions not exposed to the sun (Azevêdo, 1980).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies have shown, however, that when a reasonably large number of microsatellites are scored the inferences from those samples, even at the worldwide level, are sound (Bowcock et al 1994;Jorde et al 2000;Rosenberg et al 2002;Ayub et al 2003;Zhivotovsky et al 2003;Shepard et al 2005;Zabala Fernandez et al 2005). For examining structure and variation within a single population or ethnic group they may be the marker of choice Destro-Bisol et al 2000;Perez-Miranda et al 2005;Li et al 2006). This study of structure and variation among Australian Aboriginals using fifteen autosomal microsatellites fulfils these requirements.…”
Section: Resultsmentioning
confidence: 99%